The clinical role of stool test (HpSA) in noninvasive diagnosis of Helicobacter pylori infection - Dino VAİRA and Chiara Ricci and Carmela ACCİARDİ and Luigi Gatta and Sonia BERARDİ and; o MİGLİOLİ (Turkish Journal of Gastroenterology, 2019)
-